Botswana Poverty Assessment - World Bank Group (World Bank, Washington, DC, 2016)
Living conditions of Botswana have improved over the past decade and poverty has reduced significantly. This decrease was accompanied by a considerable decline in both depth and severity of poverty, indicating that consumption has improved among the poor. While rural areas led the poverty reduction, the share of the poor living in urban areas has increased. Botswana’s progress toward reduction of extreme poverty and inequality was among the world’s strongest in the second half of 2000s. During this period, the economic growth has been strongly pro-poor. Botswana is one of the top performers in Africa when measured by annual consumption distribution growth for the bottom 40 percentile. However, despite these noteworthy improvements, inequality remains high. The study concludes that with adequate macro and social policies, and a strong focus on improving equity, Botswana has a historical opportunity to build on recent achievements and move towards eradicating extreme poverty within one generation. The analyses was conducted in close collaboration with the Statistics Botswana, utilizing the data generated through the nationally representative households income and expenditure surveys conducted by Statistics Botswana in 2002/2003 and 2009/2010. The report benefited greatly from the leadership by the Poverty Eradication Unit.